Effectiveness of E-Learning-Based Learning in the Era of Digital Transformation: A Meta-Analysis - Setyawan, Herlin; Sukardi; Risfendra; Jalinus, Nizwardi; Mardizal, Jonni; Ananda, Gheri Febri (Indonesian Journal of Educational Research and Review, 2024)
Amid digital transformation in the 21st century, the use of digital technology, such as e-learning, in the learning process has become urgent to develop vocational school students' knowledge and skills. However, some studies show that online learning is ineffective in improving vocational school students' knowledge and skills. Online learning cannot improve students' vocational skills because the online learning process cannot conduct actual practicum. Therefore, this study aims to analyze the effectiveness of online learning to improve vocational students' knowledge and skills. The research method used was random effect model meta-analysis with Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) article analysis technique. A total of 25 articles from the Scopus, Google Scholar, and Wiley databases were obtained and analyzed in this study. The articles analyzed were free from publication bias, as indicated by the funnel plot, Egger's, and Fail-safe N test results. Based on the meta-analysis results, it is known that the effect size value obtained is 0.703 (medium category). Thus, implementing online learning in vocational schools has a moderate impact on improving vocational students' knowledge and skills. The findings of this study indicate that the implementation of online learning in vocational schools can support the effectiveness of learning in vocational schools and encourage students to develop the knowledge and skills they will master. This research is expected to be the basis for teachers and vocational schools to integrate online learning into the learning process.